FRI0193 Osteoblasts Promote New Bone Formation at Sites of Cartilage and Bone Erosions While Fat Marrow is Found Within the Subchondral Bone Marrow in Ankylosing Spondylitis. (9th June 2015) - Bleil, J.; Maier, R.; Hempfing, A.; Sieper, J.; Appel, H.; Syrbe, U.
Abstract : Background: Ankylosing spondylitis (AS) is characterized by erosive bone damage followed by bone formation. A recent MRI study suggested that ankylosis of sacroiliac joints develops following repair of erosions with fat metaplasia and backfill as intermediary steps in this pathway [1]. Objectives: In this study we used histological analysis of facet joints of AS patients to elucidate the mechanism of bone formation and the potential role of adipogenic tissue transformation. Methods: Sections of facet joints which can also undergo ankylosis in AS were used from patients with AS, patients with osteoarthritis (OA) and from controls (CO). In safranin O stained tissue sections, the subchondral bone marrow area and sites of erosions were evaluated with regard to replacement by fibrous tissue, a pathological feature described before, and adipogenic tissue transformation. To identify putative bone forming cells we analyzed the expression of Runx2 a shared marker of chondrocytes and osteoblasts, and collagen type X and MMP13 as specific markers of hypertrophic chondrocytes as well as CD56 and collagen 1 as markers of osteoblasts within eroded areas of the subchondral endplate and the articular cartilage. Results: Within the subchondral bone marrow adipogenic tissue transformation as well as fibrous transformation was found: 10/16 (62.5%) of CO joints, 18/29 (62%) of AS joints and 16/17 (94%) of OA joints showed replacement of bone marrow by fat marrow of various extend (up 100% of the bone marrow area/slide) while 0/16 (0%) of control joints, 12/29 (41.4%) of AS joints and 14/17 (82%) of OA joints showed transformation into fibrous tissue. Among AS joints, replacement of bone marrow by fibrous tissue was found more often in joints with cartilaginous fusion (5/6) compared to joints with bony fusion (4/15, p<0.05) while there was no difference for the incidence of fat marrow (p>0.05). At sites of subchondral bone and cartilage erosion we always found fibrous tissue. Runx2 + cells were detectable at the borders of fibrous tissue in AS and OA joints. The lack of collagen type X and MMP13 expression but osteocalcin and collagen type I expression of these cells proved the osteoblastic nature of these cells. Formation of new bone was found at contact areas between fibrous tissue and eroded articular cartilage – a phenomenon occurring more often in AS joints than in OA joint, i.e. in 92% of AS joints and 27% of OA joints (p<0.003) with fibrous tissue-cartilage contacts. Conclusions: In AS, osteoblasts lining the fibrous tissue facilitate bone formation at sites of bone and cartilage erosions which promotes joint ankylosis. Fat marrow is rather found within the adjacent subchondral bone marrow. References: Maksymowych WP, Wichuk S, Chiowchanwisawakit P, Lambert RG, Pedersen SJ: Fat metaplasia and backfill are key intermediaries in the development of sacroiliac joint ankylosis in patients with ankylosing spondylitis. Arthritis Rheumatol 2014, 66(11):2958-2967. Disclosure of Interest: None declared